2015
DOI: 10.5194/tc-9-25-2015
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying mass balance processes on the Southern Patagonia Icefield

Abstract: Abstract. We present surface mass balance simulations of the Southern Patagonia Icefield (SPI) driven by downscaled reanalysis data. The simulations were evaluated and interpreted using geodetic mass balances, measured point balances and a complete velocity field of the icefield for spring 2004. The high measured accumulation of snow of up to 15.4 m w.e. yr −1 (meters water equivalent per year) as well as the high measured ablation of up to 11 m w.e. yr −1 is reproduced by the model. The overall modeled surfac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
102
4
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(121 citation statements)
references
References 40 publications
14
102
4
1
Order By: Relevance
“…These values are 1 order of magnitude larger (more negative) than the values reported for the rest of the glaciers in the Southern Andes and do not follow the decreasing north-south trend found for smaller glaciers by Mernild et al (2015). Schaefer et al (2015) suggested that calving fluxes, which apparently increased in the last decade, are probably the cause of the high mass loss of the southern Patagonian ice field, which according to their mass balance model showed an overall positive surface mass balance between 1975 and 2011.…”
Section: Mass Balance Of Monte Tronador Glaciers In a Regional Perspecontrasting
confidence: 38%
“…These values are 1 order of magnitude larger (more negative) than the values reported for the rest of the glaciers in the Southern Andes and do not follow the decreasing north-south trend found for smaller glaciers by Mernild et al (2015). Schaefer et al (2015) suggested that calving fluxes, which apparently increased in the last decade, are probably the cause of the high mass loss of the southern Patagonian ice field, which according to their mass balance model showed an overall positive surface mass balance between 1975 and 2011.…”
Section: Mass Balance Of Monte Tronador Glaciers In a Regional Perspecontrasting
confidence: 38%
“…Direct glaciological observations in this remote region are still scarce, mainly due to the region's inaccessibility and its harsh climate (Buttstädt et al, 2009;Mernild et al, 2015;Schaefer et al, 2015). In recent decades, remote sensing techniques have enabled the spatial coverage of glaciological observations to be extended.…”
Section: Introductionmentioning
confidence: 99%
“…Of 69 major outlet glaciers in the region, 49 flow into lakes and the rest flow into the ocean (Warren and Aniya, 1999). Most of the calving glaciers have been retreating over the last several decades (Aniya et al, 1997;Rignot et al, 2003;Masiokas et al, 2009;Lopez et al, 2010) as a result of warming climate (e.g., Lopez et al, 2010;Schaefer et al, 2015). For example, Glaciar Upsala, a freshwater calving glacier in the Southern Patagonia Icefield (SPI), has been retreating and thinning since 2008, at rates significantly greater than those of other glaciers in Patagonia (Muto and Furuya, 2013;Sakakibara et al, 2013;Sakakibara and Sugiyama, 2014), and mass loss from this glacier accounted for about 15% of the total mass loss from the SPI between 2000 and 2012 (Willis et al, 2012).…”
Section: Introductionmentioning
confidence: 99%